Bridging yield gap of winter maize using improved agronomic management practices - Devkota, Richa; Pandey, Prem; Karki, Tika Bahadur; Marahatta, Santosh; Sah, Shrawan Kumar (Journal of Agriculture and Natural Resources, 2021)
Appropriate combinations of inputs determine the productivity of crops. A field experiment was carried out to evaluate the effect of different combinations of inputs on the yield of winter maize at National Maize Research Program (NMRP), Rampur, Chitwan. The experiment was laid out in randomized complete block design with four replications comprising of six treatments (T1= Hybrid (H) + recommended doses of NPK (RD) + irrigation (I) + high density (HD) (83333 plant ha-1) + improved weed management practice (IWMP), T2=Open pollinated variety (OPV)+RD+I+HD+IWMP, T3=OPV+ farmer’s doses of NPK (FD)+I+HD+IWMP, T4= OPV+FD+rainfed (R)+HD+IWMP, T5=OPV+ FD+ R+low density (LD) (55555 plant ha-1) + IWMP, T6=OPV+FD+R+LD+ farmer’s weed management practice (FWMP). The research result revealed significant variation on the grain yield among the different treatments. The highest grain yield (5357 kg ha-1) was obtained when hybrid maize was grown with recommended dose of fertilizer, higher density, irrigation and improved weed management practices. This treatment was followed by replacement of OPV in the above treatment (4410.77 kg ha-1). The decline in yield due to replacement of OPV from hybrid was 17.67 percent. The percent yield decline from full Package of practices (T1) were 23.01, 47.81, 36.66 and 35.95 when input combinations OPV+FD+I+ HD+IWMP, OPV + FD+R+HD+IWMP, OPV+FD+R+LD+IWMP and OPV+FD+R+LD+ FWMP respectively were used..The contrast for grain yield between hybrid vs. OPV, RD vs. FD and Irrigated vs. Rainfed were significant. Therefore, present investigation showed hybrid maize, recommended dose of fertilizer and irrigation were the most important inputs for improving maize productivity in winter season in Chitwan like climatic condition.